2009
DOI: 10.1177/0021955x09350805
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Reactivity, Mechanical and Fire Properties of Pu Flexible Foam

Abstract: Regarding the increasing demands for the fire resistance polyurethane foam for train and airplane industry and a serious planning to phase out the halogenated flame retardants (FR) because of high and toxic smoke generation, the use of halogen-free fire retardants have been more investigated in recent years. In this work, we have concentrated more on two well-known solid halogen-free fire retardants, expandable graphite, and melamine with two grades of each one and compare their performance in a variety of are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…OCS, spherical shape was observed in all the samples wit h respect to the unmodified PUF F . Cell window, strut and strut joint were found in all the images with resp ect to the samples additionally confirms developed one at the laboratory level is PUF F [20]. …”
Section: Morpholog Ysupporting
confidence: 76%
“…OCS, spherical shape was observed in all the samples wit h respect to the unmodified PUF F . Cell window, strut and strut joint were found in all the images with resp ect to the samples additionally confirms developed one at the laboratory level is PUF F [20]. …”
Section: Morpholog Ysupporting
confidence: 76%
“…Price et al proposed that interaction occurred between MEL and the evolved toluene isocyanate fraction arising from the decomposition of FPUF, and this leads to the suppression of the smoke and CO which mainly originated from toluene isocyanate. Moreover, Bashirzadeh and Gharehbaghi concluded that EG addition in FPUF increased CO/CO 2 rate and MEL reduced smoke generation and CO/CO 2 rate compared with pure FPUF. Gharehbaghi et al also concluded that EG‐loaded FPUF created more CO than MEL‐loaded FPUF and MEL‐loaded FPUF created less toxic gases than EG‐loaded FPUF as well.…”
Section: Introductionmentioning
confidence: 99%
“…The Al-containing additive is also discussed in [4], which forms cellulose materials [5] (sample 4 in Table 1) after reaction with oxygen. The Zn-containing one is usually the thermal-resistant hydrate ZnO-H 2 O (sample 4), with similar F R C ( C R 2 5 r u b b e r ) Y e l l o w results coming from [6].…”
Section: Resultsmentioning
confidence: 99%